KANDUNGAN SENYAWA FLAVONOID PADA DAUN MELINJO (Gnetum gnemon L.) BERDASARKAN PERBEDAAN TEMPAT TUMBUH - Mersy T Tanamal; Pamella Mercy Papilaya; Alwi Smith (BIOPENDIX, 2017)
Background: The village of Latuhalat and Kayu Putih village is a place that is on the beach and in the mountains. Potential natural resources are quite a lot of plants melinjo (Gnetum gnemon L). This study aims to determine the total compound of flavonoid content of leaf melinjo (Gnetum gnemon L) based on place difference. Method: The method used in this study using the method of Chang et al. The solvent used for diluting the melinjo extract was methanol solvent, then measured using a UV-VIS spectrophotometer. Result: Result of analysis of flavonoid compound content, Latuhalat Village has average total flavonoid content of13.080% and average total flavonoid content in Kayu Putih Village equal to 17.028%. Kayu Putih Village has more flavonoid compound than Latuhalat Village. Conclusion: Total levels of melinjo leaf flavonoids (Gnetum gnemon L) in Kayu Putih Village were more than total flavonoids of leaf melinjo (Gnetum gnemon L) in Latuhalat Village.